ถอดบทเรียนการขับเคลื่อนชุมชนเกษตรคาร์บอนต่ำภายใต้แนวคิดเกษตรทฤษฎีใหม่: กรณีศึกษา ตำบลคลองน้อย อำเภอเมือง จังหวัดสุราษฎร์ธานี - มาศชนก ขาวทอง (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The objectives of this research article were to 1) conduct lesson learned of being a low-carbon agricultural community of Khlong Noi Community, Mueang District, Surat Thani Province; 2) suggest guidelines on driving an agricultural community to a low-carbon agricultural community. For the implementation method, this is a qualitative research conversations. The research was conducted by a survey on the area, along with studying agricultural patterns from the learning center.  The achievement of the learning center was analyzed by Theory of Change The findings revealed that this role-model community was originated from the establishment of a learning center to solve problems of crop price and chemical use among local agriculturists, Until the public sector participated in resources and education for the concept of participation with communities from planning, implementation; along with community support based on the needs of local agriculturists, cooperation for driving agricultural activities, association of the people sector to acknowledge the problems and solutions, The key factors of success found in driving a low-carbon agricultural community included (1) leadership and competencies of learning center leaders, and (2) the roles of public alliance to support the community based on the needs of local agriculturists.